Biodistribution and imaging with (123)I-ADAM: a serotonin transporter imaging agent - Newberg, Andrew B; Plössl, Karl; Mozley, P David; Stubbs, James B; Wintering, Nancy; Udeshi, Michelle; Alavi, Abass; Kauppinen, Tomi; Kung, Hank F (The Journal of nuclear medicine (1978), 2004)
2-((2-((Dimethylamino)methyl)phenyl)thio)-5-(123)I-iodophenylamine ((123)I-ADAM) is a new radiopharmaceutical that selectively binds the central nervous system serotonin transporters. The purpose of this study was to measure its whole-body biokinetics and estimate its radiation dosimetry in healthy human volunteers. The study was conducted within a regulatory framework that required its pharmacologic safety to be assessed simultaneously. The sample included 7 subjects ranging in age from 22 to 54 y old. An average of 12.7 whole-body scans were acquired sequentially on a dual-head camera for up to 50 h after the intravenous administration of 185 MBq (5 mCi) (123)I-ADAM. The fraction of the administered dose in 13 regions of interest (ROIs) was quantified from the attenuation-corrected geometric mean counts in conjugate views. Multiexponential functions were iteratively fit to each time-activity curve using a nonlinear, least-squares regression algorithm. These curves were numerically integrated to yield source organ residence times. Gender-specific radiation doses were then estimated with the MIRD technique. SPECT brain scans obtained 3 h after injection were evaluated using an ROI analysis to determine the range of values for the region to cerebellum. There were no pharmacologic effects of the radiotracer on any of the subjects, including no change in heart rate, blood pressure, or laboratory results. Early planar images showed differentially increased activity in the lungs. SPECT images demonstrated that the radiopharmaceutical localized in the midbrain in a distribution that is consistent with selective transporter binding. The dose-limiting organ in both men and women was the distal colon, which received an average of 0.12 mGy/MBq (0.43 rad/mCi) (range, 0.098-0.15 mGy/MBq). The effective dose equivalent and effective dose for (123)I-ADAM were 0.037 +/- 0.003 mSv/MBq and 0.036 +/- 0.003 mSv/MBq, respectively. The mean adult male value of effective dose for (123)I-ADAM is similar in magnitude to that of (111)In-diethylenetriaminepentaacetic acid (0.035 mGy/MBq), half that of (111)In-pentetreotide (0.81 mGy/MBq), and approximately twice that of (123)I-inosine 5'-monophosphate (0.018 mGy/MBq). The differences in results between this study and a previous publication are most likely due to several factors, the most prominent being this dataset used attenuation correction of the scintigraphic data. Region-to-cerebellum ratios for the brain SPECT scans were 1.95 +/- 0.13 for the midbrain, 1.27 +/- 0.10 for the medial temporal regions, and 1.11 +/- 0.07 for the striatum. (123)I-ADAM may be a safe and effective radiotracer for imaging serotonin transporters in the brain and the body.